Development Performance of Agriculture and Fisheries as Leading Program of Local Government and their Impact on People’s Lives in Gorontalo Province, Indonesia - Jusdin Puluhulawa; Hayatiningsih Gubali; Mohamad Ikbal Bahua (Hasanuddin University, 2017)
This research discusses two problems, namely the construction performance of agricultural and fisheries development and (2) their impact on community. The research employed qualitative research. The results showed that attainment of agricultural performance in the last five years, gave a quite significant impact on community. Along with the extensive development of the harvest and production, especially for commodity corn, growing on average per year (2012-2016) of 54.8% reached 548,220 tons each year. Agricultural performance has given the economic impact to farmers, with contribution of agricultural sector in gross regional product of Gorontalo Province (30.35% per annum). For the fisheries sector, the fisheries development is shown by the last of five years (2012- 2016), both capture fisheries or fishing areas, the average growing 59,228.6 tons per year. The performance of this economic impact on fishing communities, demonstrated by the contribution of fisheries to GDP of the Province (2012-2016) of 20.06% per year, and per capita income grew an average of Rp 12.51% per year. The second performance of the program impact was significant for society, particularly in the field of education, which is shown by the development of the school's participation numbers, the rate of literacy, and the use of education facilities of community expenditure above 95%.